(untitled) (Journal of the College of Basic Education, 2023)
Ethical values ​​are human, general and without specification, but there are moral values ​​with certain characteristics that are monopolized by nations over others, by virtue of their innate and civilized readiness, due to a difference in thinking and reasoning, and a difference in understanding and perception. At a time when some moral values ​​are subject to factors of change, modification or decay; Motivated by the course of time and its rapid development, there are moral values ​​other than them that are not subject to change, nor are they dealt with by change, nor are they subject to decay. Being fixed in origins, well-established roots, eternal influence on souls and minds.These fixed moral values ​​necessarily affect the behavior of man, and draw him strongly to his lived reality, with his full thought and feeling, and help him to rise above what detracts from his dignity and dignity, and takes him by the hand to reassurance, tranquility and success.